Dual-Band CPW-Fed Transparent Antenna for Active RFID Tags - Malek, M. A. (Institute of Electrical and Electronics Engineers Inc., 2015)
A dual-band coplanar-waveguide (CPW)-fed transparent antenna for active radio-frequency identification (RFID) tags working at 2.45 GHz and 5.8 GHz is proposed. AgHT-8 thin film, includes the silver-coated polyester as the conductive layer, and polyethylene terephthalate as the substrate, is used to design and fabricate the antenna with high transparency of above 80%, which is sufficient to provide the ability to laminate the surface of the tag devices with little chance of detection. The overall dimension size of the proposed design is 36 × 39 × 0.175mm3. The measured bandwidth of 59.34% (1.6 to 2.95 GHz) and 16.95% (5.4 to 6.4 GHz) is achieved for the lower band and the upper band, respectively. The proposed antenna has considerably less thickness and a lighter structure compared with the nontransparent designs.